Annealing effects on the optical and electrochemical properties of tantalum pentoxide films - Ren, Wei; Yang, Guang-Dao; Feng, Ai-Ling; Miao, Rui-Xia; Xia, Jun-Bo; Wang, Yong-Gang (Journal of advanced ceramics, 2021)
Tantalum pentoxide (Ta 2 O 5 ) has attracted intensive attention due to their excellent physicochemical properties. Ta 2 O 5 films were synthesized via electron beam evaporation (EBE) and subsequently annealed at different temperatures ranging from 300 to 900 °C. X-ray diffraction (XRD) results show that amorphous Ta 2 O 5 thin films form from 300 to 700 °C and then a phase transition to polycrystalline β-Ta 2 O 5 films occurs since 900 °C. The surface morphology of the Ta 2 O 5 films is uniform and smooth. The resulted Ta 2 O 5 films exhibit excellent transmittance properties for wavelengths ranging from 300 to 1100 nm. The bandgap of the Ta 2 O 5 films is broadened from 4.32 to 4.46 eV by annealing. The 900 °C polycrystalline film electrode has improved electrochemical stability, compared to the other amorphous counterparts.